Response to the experimental inoculation of Sigmodon hispidus (Rodentia: Muridae) with vesicular stomatitis virus, New Jersey serotype - Salman, M. (2009)
Sigmodon hispidus (cotton rat) was previously found to have antibodies against Vesicular Stomatitis Virus, New Jersey serotype (VSV-NJ) under field conditions in Costa Rica. In order to evaluate their response to the virus and potential role as reservoirs, a total of 30 adult laboratory-raised cotton rats were experimentally inoculated with 107 TCID50/ml VSV-NJ, Greentree strain, as follows: 10 by subcutaneous route (group A), 10 by oral abrasion (group B) and 10 by intranasal route (group C). Two negative control animals were included in each group. Animals developed neutralizing antibody titers ranging between 1:10-1:2560 six days after the inoculation. This species showed an immune response to Vesicular Stomatitis Virus by increasing antibody titers after inoculation, and most individuals maintained their antibody titers over time. However, live virus and replication of the virus in the host could not be demonstrated by virus isolation attempts in tissue culture methods. Hyperactivity was the only clinical sign observed in the subcutaneous and oral abrasion groups. The intranasal group presented dyspnea, depression, and weight loss. In this group, 7 of the inoculated animals died 6 days post inoculation and the last one died on day 37 post inoculation. The necropsy of the animals in this group revealed pneumonia, hyperemia in the intranasal bone, and cerebral and hepatic congestion. Control animals did not show antibody development or clinical signs. After 122 days post-inoculation, case fatality rate was 12.5% in group A, 43% in group B, and 100% in group C.